The influence of natural and anthropogenic factors on demersal fauna in the western English Channel and Celtic Sea - Fincham, Jennifer I.; Veneziano, Alessio; Ellis, Jim R. (Journal of sea research, 2020)
Displacement of fisheries through management has the potential to re-distribute the anthropogenic pressures associated with fishing practices. These anthropogenic pressures occur concurrently with naturally occurring environmental processes, and their combined influences can alter the structure of species assemblages across a region. Spatial variability in the demersal assemblages in the Celtic Sea and western English Channel were examined in relation to the influence of abrasion (relating to trawling pressure from bottom-towed fishing gears) and natural hydrodynamic processes (using kinetic energy as a measure of bed shear stress) using canonical correspondence analysis. Kinetic energy graduated from low levels in the western part of the study area to higher levels in the east, whilst trawling pressure varied at smaller spatial scales largely focussed on fishing grounds. Species assemblages were correlated with kinetic energy, with some species of commercial value being more strongly associated with areas subject to increased trawling pressure. However, the species assemblages at similar stages along this gradient of kinetic energy differed between ICES Divisions within the study area. Due to these regional differences, any management measures that may result in the re-distribution of fishing pressure should consider the potential impact on those assemblages (and associated species) that may then be subject to increased fishing disturbance. •Fauna assemblages with similar natural disturbance differed between ICES Divisions.•Trawling pressure varies at small spatial scales.•Demersal species assemblages were correlated with natural disturbance.